1994
DOI: 10.1161/01.cir.89.6.2582
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic significance of detection of enteroviral RNA in the myocardium of patients with myocarditis or dilated cardiomyopathy.

Abstract: These data demonstrate that the detection of enterovirus RNA in the myocardium of patients with heart muscle disease at the time of initial investigation is associated with an adverse prognosis and that the presence of enterovirus RNA is an independent predictor of clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
121
1
13

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(141 citation statements)
references
References 46 publications
2
121
1
13
Order By: Relevance
“…These results provide a new basis by which previous detection of enteroviral RNA in cardiomyopathic heart tissue in the absence of infectious virus (4, 60, 92) may be evaluated. Picornavirus infections are generally considered to be acute and cleared rapidly by the host adaptive immune response, yet long-term persistence in animals and humans has been demonstrated (4,54,60,87,92,95,104,116). The mechanism by which long-term picornavirus persistence occurs in the presence of an intact immune system remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results provide a new basis by which previous detection of enteroviral RNA in cardiomyopathic heart tissue in the absence of infectious virus (4, 60, 92) may be evaluated. Picornavirus infections are generally considered to be acute and cleared rapidly by the host adaptive immune response, yet long-term persistence in animals and humans has been demonstrated (4,54,60,87,92,95,104,116). The mechanism by which long-term picornavirus persistence occurs in the presence of an intact immune system remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious enteroviruses are frequently isolated from pediatric cases of human myocarditis, but isolation from adult cases of the disease has been exceedingly rare (34,62,88), perhaps because pediatric cases may be more likely to be diagnosed during the acute infection. Despite an apparent absence of infectious enterovirus that can be isolated from adult cardiomyopathies, the detection of positive-and negative-strand enteroviral RNA in approximately 20% of adults with myocarditis or dilated cardiomyopathy by reverse transcription-PCR (RT-PCR) (87,116) as well as the detection of enteroviral protein in cardiomyopathic heart muscle (4,60) provides evidence that enteroviruses can persist and replicate in the heart in the apparent absence of infectious virus. CVB can persist for long periods of time in different strains of mice (22,55,69,95,104).…”
mentioning
confidence: 99%
“…1,2 It has been demonstrated that the detection of EV RNA in myocardium of DCM patients is associated with adverse prognosis. 3 In particular, the presence of minus-strand EV RNA indicates active viral replication, and plays a role in the development of myocardial injury in DCM. 4 Our previous study has reported that myocardial expression levels of tumor necrosis factor-a (TNF-a) and EV RNA were increased in patients with DCM regardless of etiology of left ventricular (LV) dysfunction.…”
mentioning
confidence: 99%
“…Among them, coxsackievirus B3 (CVB3)-a member of the picornavirus family-is one of the most important causes of virus-induced acute or chronic myocarditis in humans (37). The presence of CVB3 in heart tissue of patients with acute myocarditis or dilated cardiomyopathy has been demonstrated, e.g., by detection of virus genome (18) and virus protein (23).…”
mentioning
confidence: 99%